Physician Preferences and Clinical Experience with Rabeprazole–Domperidone in Acid-Related Disorders: Insights from the Power Physician Survey 3.0 in India (Indian Journal Of Clinical Practice, 2026)
Gastroesophageal reflux disease (GERD) is a common and chronic acid-related disorder that significantlyaffects quality of life. Proton pump inhibitors (PPIs) remain the cornerstone of therapy, often prescribed in combination withprokinetics such as domperidone to enhance symptomatic relief. This survey aimed to assess physician perceptions, prescribingpatterns, and key factors determining the choice of PPI–domperidone combinations in India. Methods: A cross-sectional,perception-based digital survey (Power Physician Survey 3.0) was conducted among 3,260 physicians across India. A structuredquestionnaire captured information on patient load, preferred treatment strategies, time to symptom relief, recurrence rates,and factors guiding the selection of specific PPI–domperidone combinations. Responses were analyzed using descriptivestatistics. Results: Over half of the respondents (51.6%) preferred prescribing a PPI–domperidone combination rather than PPImonotherapy. The rabeprazole–domperidone (RD) combination emerged as the most preferred regimen (80.1%), primarily forits rapid acid inhibition (46.6%), better tolerability (18.3%), and cost-effectiveness (13%). About half of the physicians observedsymptomatic relief within 2 to 3 days (50.6%), with 82.8% perceiving lower recurrence rates and 88.7% reporting improvedpatient adherence. On preference ranking, RD was selected as the first choice by 80.1% of physicians, followed by pantoprazole–domperidone (10.4%), omeprazole–domperidone (4.8%), and esomeprazole–domperidone (4.7%). The combination was alsorated most effective for night-time heartburn (90%) and preferred for patients with comorbidities (86.3%). Conclusion: Thefindings highlight a strong real-world preference for the RD combination in GERD management, driven by its rapid action,safety, and patient-centered benefits including improved adherence, symptom control, and reduced recurrence. These insightsemphasize the importance of balancing efficacy, tolerability, and affordability in clinical decision-making for acid-relateddisorders in India.